Deliberately infecting healthy volunteers with malaria parasites: Perceptions and experiences of participants and other stakeholders in a Kenyan‐based malaria infection study. (9th July 2020) - Jao, Irene; Marsh, Vicki; Che Chi, Primus; Kapulu, Melissa; Hamaluba, Mainga; Molyneux, Sassy; Bejon, Philip; Kamuya, Dorcas
Abstract : Controlled human malaria infection (CHMI) studies involve the deliberate infection of healthy volunteers with malaria parasites under controlled conditions to study immune responses and/or test drug or vaccine efficacy. An empirical ethics study was embedded in a CHMI study at a Kenyan research programme to explore stakeholders' perceptions and experiences of deliberate infection and moral implications of these. Data for this qualitative study were collected through focus group discussions, in‐depth interviews and non‐participant observation. Sixty‐nine participants were involved, including CHMI study volunteers, community representatives and research staff. Data were managed using QSR Nvivo 10 and analysed using an inductive‐deductive approach, guided by ethics literature. CHMI volunteers had reasonable understanding of the study procedures. Decisions to join were influenced by study incentives, trust in the research institution, their assessment of associated burdens and motivation to support malaria vaccine development. However, deliberate malaria infection was a highly unusual research strategy for volunteers, community representatives and some study staff. Volunteers' experiences of physical, emotional and social burdens or harms were often greater than anticipated initially, and fluctuated over time, related to specific procedures and events. Although unlikely to deter volunteers' participation in similar studies in furture, we argue that the dissonance between level of understanding of the burdens involved and actual experiences are morally relevant in relation to community engagement, informed consent processes, and ongoing support for volunteers and research staff. We further argue that ethics oversight of CHMI studies should take account of these issues in deciding whether consent, engagement and the balance of benefits and harms are reasonable in a given context.